Narrative harmony: Empowering students through the national anthem in social studies education - Wiyanarti, Erlina; Mutiani, Mutiani; Abbas, Ersis Warmansyah; Holilah, Mina; Salman, Nola Fibriyani Bte (Jurnal Teori dan Praksis Pembelajaran IPS, 2023)
This study explores the integration of the national anthem into social studies education. It is essential, considering that the coverage of IPS material is related to the fighting spirit of citizens. The article describes the relevance of the national anthem and the material in social studies learning. The article was prepared by utilizing 20 pieces of literature. The literature is devoted to studies relevant to the national anthem used in learning. The research results show that social studies education's relevance in integrating the National Anthem plants the seeds of lifelong civic responsibility. This study argues that once used only in classrooms, national anthems now serve as a guiding force, empowering students to contribute to their nation's ongoing narrative actively. The Indonesian national song "Dari Sabang to Merauke" examines its geographic and nationalist meaning. Using this song as a resource will increase meaningful social studies learning, including aspects of Indonesia's geography, history, and cultural diversity. This study identifies the impact of integrating the national anthem on student engagement, emphasizing the instillation of civic responsibility.